Analisis Strategi Dakwah Gus Ahmad Rifai dalam Wadah Konco Ngaji Terhadap Meningkatnya Kecintaan Anak Muda - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Muhammad Yusuf Qordhowi; Muhammad Firdaus H; Ditho Anung Cahyadi (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
cientific research entitled “Analysis of Gus Ahmad Rifai’s da’wah strategy in the gathering of Konco Ngaji towards increasing young people’s love for religion” aims to find out what is called the Konco Ngaji assembly and to find out the influence of the konco ngaji assembly on increasing the knowledge and manners of the congregation. This scientific research the writer did using a qualitative approach method. The source of scientific research material used is in the form of primary data by conducting observations and interviews with parties involved in the Konco Ngaji Assembly. The results of the scientific research carried out by the author are as follows: First, the Konco Ngaji Assembly is an assembly of knowledge that prohibits anything related to the Islamic religion, and also prohibits young people from loving Islam, which is guided by Gus Ahmad Rifai. Second, from the results of interviews with five members of the congregation who recite the Konco Ngaji, that this assembly has a major influence on changing the character and thinking of young people, making young people think more broadly and have Islamic morals, following the right path as taught by the Prophet Muhammad SAW.